Computer simulations of Li-Mn-O layered-spinel composite nanoarchitectures - Hlungwani, Donald (My University, 2020)
Layered-spinel composite electrodes are among the promising cathode materials for advancing lithium-ion batteries due to the reported synergistic effect, which contributes to improvement of their electrochemical performance. A vast number of studies have focused on strategies to enhance the specific capacity of layered-spinel composite cathode materials. However, limited efforts have been put into understanding the impact of structural changes incurred by the material during the discharge process. Consequently, this work is aimed at studying the discharge process of a lithium-ion battery utilising, particularly the nanoarchitectured composite Li-Mn-O layered-spinel cathode material using the simulated synthesis technique. The structural changes (electronic level and atomic level) affecting electrochemical performance as the discharge process proceeds are captured. The electronic structure of the magnetic and non-magnetic Mn2O4, LiMn2O4 and Li2Mn2O4 have been investigated. For the electronic level, the discharge process was depicted by the Mn2O4, LiMn2O4 and Li2Mn2O4 spinel structures and structural changes were analysed through electronic band structures and density of states. The amorphisation and recrystallisation technique was also performed to enable the atomic-level structural analysis. Consequently, Li-Mn-O layered-spinel composite nanoarchitectures depicting different stages of the discharge process in question were generated. From the calculated density of states and electronic band structures, all the non-magnetic structures show metallic behaviour with the filling of the conduction band increasing with lithiation. The electronic structure of the magnetic Mn2O4 spinel structure exhibits semiconducting properties which are in line with literature. The electronic band structures and density of states (DOS) of the magnetic LiMn2O4 and lithiated-Li2Mn2O4 reveal metallic behaviour with the Fermi level mainly comprising of spin-down states. The discharge process was simulated by performing a chemical lithiation on the LiMn2O4 amorphous spinel structure succeeding the amorphisation process. The simulated recrystallisation was then performed on the lithiated amorphous LixMn2O4 spinel structures, where 1 ≤ x ≤ 2. The recrystallisation process yielded multigrain nanospheres constituting Li-Mn-O layered and spinel components confirmed by atomic structural snapshots and X-ray Diffraction (XRD) Patterns. The amorphous and crystalline states of these systems were verified by Radial Distribution Functions (RDFs) and XRD patterns. The spontaneous recrystallisation process was illustrated by configuration energy graphs indicating nucleation and crystal growth stages as the process progresses. Configuration energy graphs show that an increase in lithium content favour’s the nucleation process resulting in less amount of time required for crystal growth. XRD patterns showed Mn3O4, LiMn2O4, and Li2MnO3 characteristic peaks revealing the co-existence of these components in the simulated nanoarchitectures. The Mn3O4 component decreases with lithium concentration and an increase in lithium concentration favour’s the formation of spinel LiMn2O4 and layered Li2MnO3 phases. A number of crystallographic vacancy defects are observed at lower lithium concentrations and they decrease with lithiation. Suggesting that lithium atoms are occupying these sites as the discharge process progresses. Clear lithium diffusion channels are noted as the discharge process proceeds which is evinced by an increase in crystallinity with lithiation.
Thesis (M.Sc. (Physics)) -- University of Limpopo, 2020
Keywords: Nanoarchitectures; Li-Mn-O layered; Radial Distribution Functions; Artificial intelligence; Computer simulation; Lithium ion batteries